Dietary supplementation of artificial sweetener and capsicum oleoresin as a strategy to mitigate the negative consequences of heat stress on pig performance - Biggs, Morgan E; Kroscher, Kellie A; Zhao, Lidan D; Zhang, Zhenhe; Wall, Emma H; Bravo, David M; Rhoads, Robert P (Journal of animal science, 2020)
Abstract Pigs exposed to elevated ambient temperatures exhibit reduced daily gain, alterations in muscle and fat deposition, and decreased health. Negative aspects of gastrointestinal (GI) function, integrity, and permeability also occur. High-intensity sweeteners can ameliorate the negative effects of heat stress (HS) by increasing GI glucagon-like peptide-2 production while capsicum oleoresin has been shown to reduce inflammatory response. The effects of an artificial high-intensity sweetener and capsicum oleoresin (CAPS-SUC; TakTik X-Hit, Pancosma, Switzerland) on growth performance of pigs were examined. Forty-eight pigs (12 wk of age, 43.2 ± 4.3 kg) were assigned to six treatments: thermoneutral conditions (21 ± 1.1 °C; 40% to 70% relative humidity) fed ad libitum with (TN+) or without supplement (TN−), heat stress (35 ± 1 °C; 20% to 40% relative humidity) fed ad libitum with (HS+) or without supplement (HS−), and thermoneutral conditions pair-fed to HS intake with (PFTN+) or without supplement (PFTN−). Supplementation (0.1 g/kg feed) began 2 d prior to the 3-d environmental treatment period. Body weights (BWs) and blood samples were collected on days −1 and 3. Rectal temperature (RT) and respiration rate (RR) were measured thrice daily and the feed intake (FI) was recorded daily. Intestinal sections were collected for histology. Pigs in HS conditions exhibited increased RT (~1.2 °C) and RR (~2.7-fold) compared with TN and PFTN groups (P < 0.01). HS+ animals had increased RR when compared with HS− animals (P < 0.02). Heat stress decreased FI compared with TN. HS and PFTN decreased (P < 0.05) average daily gain compared with TN. Supplement did not alter the BW gain. HS and PFTN decreased (P < 0.05) Gain:Feed compared with TN during environmental treatment. Supplementation with CAPS–SUC increased Gain:Feed by 0.12 (P < 0.05). Circulating glucose concentrations tended to decrease in CAPS–SUC vs. non-supplemented HS and PFTN animals (P ≤ 0.1). Circulating insulin concentrations as well as monocyte count increased in HS compared with PFTN (P < 0.04) but did not differ from TN and likely linked to altered FI. CAPS–SUC increased basophil count (P < 0.02), irrespective of environment. Ileal villus height tended to decrease during HS and PFTN compared with TN (P < 0.08), indicating an effect of intake. Overall, CAPS–SUC supplementation increased pig feed efficiency and may improve immune response.